Protection for seller and buyer in online transaction: Malaysian perspective - Abdullah Asuhaimi, F.; Pauzai, N.A.; Asari, K.N.; Makhtar, M. (2016)
Since the emergence of electronic commerce, a massive development and a considerable increase has occurred in every aspect of business life worldwide. The application of commercial activities via the World Wide Web (Internet), in particular, has played a significant part in the development of the commercial and economic sectors in many parts of the world. Although the Internet has become a convenient method for doing business for many people, such as paying bills, buying items through online catalogs or merchants, trading on the stock market, or just browsing or chatting with others online, the Internet also provides the opportunity for big fraud and cheat. The authors in this paper highlighted the most common problems occurred in online transaction and suggest few approach for its solution. Thus, the authors adopted qualitative research method to gather data in writing this paper. Among the most common problems are security issues, no price is display, items received not in a good condition, buyer did not received the products, wrong description of products, and no quality products. This paper also discuss on the legislation provided by the Malaysian authorities to deal with this problems and also ways to solve most of the problems in online transaction.